Narrativas de escolarização : relação com os saberes compartilhados por alunos e alunas nas aulas de educação física - Santos, Veronica Freitas dos (2013)
This paper is caracterized for being a study of quantity-quality aproach. The teoric-metodologic pressuposition utilised is the autobiographic narrative and will be constituted from a historic perspective. It have as objective understand the process of the student’s learning related to the knowleges shared in Physical Education, during the period of schooling. To do that, we analise the the third year of Secondary School’s student’s narratives of a public school in Serra, to describe their experiences with the subject during their school lifes. We bring as main interlocutors the dialog with Walter Benjamin in the understanding of the narrative, with Bernard Charlot and their studies about the relation with the knowlege and Michel de Certeau in the operational logics in the daily routine and the story’s writing. The results have shown that the relation with the knowlege and the identities created to Physical Education are correlated in historical movement, tensioned by schollar logic and by the student’s experiences, which results in loss of interess in Physical Education’s classes during the ongoing of schooling.